Faktor-Faktor Yang Mempengaruhi Implementasi SAK EMKM Pada Usaha Mikro, Kecil, dan Menengah - Arini, Arini; Isyanto, Puji; Arimurti, Trias (Gorontalo Accounting Journal, 2025)
The aim of this research is to determine the factors that influence the implementation of SAK EMKM among MSMEs in East Karawang District, including understanding of accounting, level of education and use of information technology. The method in this research is a quantitative method of primary data resulting from distributing questionnaires. This research hypothesis was tested using multiple linear regression analysis with the SEM EViews version 12 program, the sampling technique was purposive sampling. The results of this research show that the accounting understanding variable influences the implementation of SAK EMKM, the education level variable influences SAK EMKM and the variable use of information technology influences the implementation of SAK EMKM. The variables understanding accounting, level of education and use of information technology jointly influence the implementation of SAK EMKM. This research helps contribute to the field of financial accounting, especially in MSMEs, by revealing empirical evidence that understanding accounting, level of education and use of information technology can implement SAK EMKM in MSMEs in East Karawang District.